Priority and delay constrained demand side management in real‐time price environment with renewable energy source. (15th July 2016) - Rasheed, Muhammad Babar; Javaid, Nadeem; Ahmad, Ashfaq; Awais, Muhammad; Khan, Zahoor Ali; Qasim, Umar; Alrajeh, Nabil
Summary: In smart grid, integration of renewable energy sources such as solar and wind is a challenging task because of their intermittent nature. Most of the existing demand side management techniques are based on day‐ahead pricing or time of use pricing that deviate from real‐time pricing because of unpredictable energy consumption trends and electricity prices. This paper presents opportunistic scheduling algorithms in a real‐time pricing environment based on optimal stopping rule. We classify different users and assign priorities based on energy demand. In order to minimize the electricity bill and appliance waiting time cost, we modify the first come first serve scheduling algorithm. Regarding comfort maximization, priority enable early deadline first scheduling algorithm is proposed, which schedules the appliances based on minimum length of operation time and priority constraints. Simulation results validate the effectiveness of the proposed algorithms in terms of electricity cost reduction and user comfort maximization. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This paper presents opportunistic scheduling algorithms in a real‐time pricing environment based on optimal stopping rule. This paper classifies different users and assigns priorities based on energy demand. This paper proposes priority enabled early deadline first scheduling algorithm to maximize user comfort. Results prove electricity cost reduction and user comfort maximization.